Management of eutocic delivery in a patient with COVID-19 in Lima, Peru - Campodonico Olcese, Lorena (2020)
We present the case of a eutocic, uncomplicated delivery in a patient positive for COVID-19. The patient, a 33-year-old woman, 39 weeks pregnant, who had received prenatal care in a private clinic, presented in labor, coughing, without any other symptoms. She was diagnosed with COVID-19 by rapid test, IgM (+) and IgG (-). We isolated the patient and provided personal protective equipment following our clinic’s protocol. Delivery was managed according to obstetric conditions, applying epidural anesthesia in the active phase; the baby was born without complications. Nor skin-to-skin contact nor delayed umbilical cord clamping were performed. Mother and child were discharged without complications after the newborn completed the required isolation period, testing negative for COVID-19. Telephone follow-up was performed. The healthcare team followed the recommended protocol to manage delivery during the COVID-19 pandemic.